Societal trust and corporate tax avoidance - Kanagaretnam, Kiridaran; Lee, Jimmy; Lim, Chee Yeow; Lobo, Gerald (Review of Accounting Studies, 2018)
Using an international sample of firms from 25 countries and a country-level index for societal trust, we document that societal trust is negatively associated with tax avoidance, even after controlling for other institutional determinants, such as home country legal institutions and tax system characteristics. We explore the effects of two country-level institutional characteristics—strength of legal institutions and capital market pressure—on the relation between societal trust and tax avoidance. We find that the relation between trust and tax avoidance is less pronounced when the legal institutions in a country are stronger and is more pronounced when the capital market pressure is stronger. Finally, we examine the relation between societal trust and tax evasion, an extreme and illegal form of tax avoidance. We show that societal trust is negatively related to tax evasion and the negative relation is less pronounced when legal institutions are stronger.